A Robust Control with the Combination of Fuzzy and SMC to Stabilize the Power System - Mohammadreza Barzegaran; Sana Tajvidi (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
Common power system stabilizer (CPSS), fuzzy power system stabilizer (FPSS) and sliding mode controller (SMC) are common controllers which are used in controlling single machine infinite bus (SMIB) power systems. Each of these controllers has disadvantages. CPSS is not robust enough to stabilize the power system perfectly. SMC is more robust than CPSS but in the presence of big uncertainties it is unable to stabilize power system. FPSS is enough robust in the presence of big uncertainties, but it causes chattering when high switching gain is needed. The goal of this paper is to present a robust controller for a single machine infinite bus (SMIB). The proposed controller is a direct fuzzy controller assisted with a sliding mode controller. The simulation shows clear positive effect and validity of the method in convergence, time and accuracy.